Taxonomy of a predaceous springtail: the revision of the Palaearctic species of Metisotoma Maynard, 1951 - Potapov, Mikhail; Babenko, Anatoly; Fjellberg, Arne; Schulz, Hans-Jürgen (Zootaxa, 2018)
Metisotoma grandiceps (Reuter, 1891), the only veritable predator among springtails, is redescribed from materials collected near the type locality (Taimyr) and from Siberia and Far East. Its distribution in Holarctic is stated and the taxonomic position is discussed. A syntype of M. macnamarai (Folsom, 1918) (Canada) and the holotype of M. ursi (Yosii, 1972) (Japan) were redescribed as far as was possible. Two new species, M. stebaevae sp. nov. and M. bermani sp. nov., from the Altai Mountains and Magadan Region are described. Labial palp, number of s-setae, macrochaetotaxy, and ventral chaetotaxy of body are considered to be of diagnostic value separating the species. Some observations of predator behavior in laboratory conditions are presented.